Exploring the relationships between Early Childhood Adversity, Social Cognition, and Aggression in a South African Study of People Living with Schizophrenia - K. van der Walt; O. Wootton; J. Rokicki; A. Vaskinn; D. Jonker; M. Campbell; E. Susser; U.K. Haukvik; R.C. Gur; D.J. Stein; C. Friestad (Schizophrenia Research: Cognition)
People living with schizophrenia (PLS) are at increased risk of being both victims and perpetrators of violence. Recent research suggests that social cognitive impairments may contribute to heightened aggression in schizophrenia. Childhood trauma, a well-established risk factor for both schizophrenia and aggression, is also linked to more severe cognitive deficits in PLS. Few studies have explored the relationships between childhood trauma, social cognition, and aggression in large sample sizes, particularly in low- and middle-income settings, where varying socioeconomic factors and exposure to violence may influence these associations. In this study, a subsample of participants (PLS = 585; controls = 882) from the Genomics of Schizophrenia in the South African Xhosa People study completed The Childhood Trauma Questionnaire (CTQ), Penn Emotion Identification Test (ER), Life History of Aggression Questionnaire (LHA), and Structured Diagnostic Interview for DSM-IV Axis I Disorders. Group differences in CTQ, ER, LHA, and selected demographic and clinical factors were assessed using t-tests and chi-square tests. Multivariable linear regressions were employed to test for associations among CTQ, ER, and LHA. We found that PLS had significantly higher childhood trauma and lifetime aggression scores and poorer emotion recognition performance than controls. Higher childhood trauma was associated with higher lifetime aggression and worse emotion recognition performance. However, emotion recognition performance was not associated with lifetime aggression. In this setting, childhood trauma predicts lifetime aggression and poorer emotion recognition, but there is no evidence that emotion recognition ability is related to aggression.